Mapping of salinity level using spline interpolation techniques over the water of Sungai Merbok, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Sharir Aizat, Kamaruddin; Khairul Naim, Abd Aziz; Muhammad Akmal, Roslani; Jamil, Tajam; Shaıdatul Najwa, Zaınolabdın; Nur Fatin Aqilah, Mohd Razman (Universiti Teknologi MARA, Perak, 2018)
Interpolation map of salinity is a helpful scientific instrument for environmental monitoring and for social economic development especially for the community who lived in Sungai Merbok. This research was conducted to develop a spatial model of salinity using spline interpolation technique. 20 sampling stations were randomly set up to measure the level of salinity using YSI 650 Multiparameter Display System (MDS). Quantitative analysis of standard regression and error index were used to evaluate the developed model. The research found that the tension splines type performed better than regularized splines type. The local government and community, who live in Sungai Merbok, can use the developed map of salinity for guidelines and future development of Sungai Merbok, Kedah.